Vietnam Union with the implementation of the representative mission, benefits of benefits and protection of interests of united states, laborers - Phạm Thị Nga (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
With the overall goal of improving the effectiveness of representation, taking care of protecting the legitimate and legitimate rights and interests of union members and workers, for sustainable jobs, the life is getting higher and higher. Accordingly, Vietnam Trade Union identified three breakthroughs in which "organizational innovation and operation mode; take care of the benefits of union members, workers' protection representatives ”is a breakthrough that needs to be carried out regularly and qualitatively.